The Sub-National Politics of Setting Road Infrastructure Development Agenda (RIDA): An Insight from Yobe State, North Eastern Nigeria (Global Journal of Human-Social Science, 2018)
Some political social and economic factors often confront democratic regimes in making decisions in their developmental strides Despite its importance however the issues of how and why road infrastructure development agenda RIDA emerged are often neglected in political discourse In Nigeria s North Eastern region and in Yobe state in particular where the availability of road infrastructure is still not adequate and financial resources and political consideration collectively require fresh insights This paper therefore provides the description and analysis of RIDA of Governor Gaidam in Yobe State from 2009-2015 through the perceptions and experiences of road development stakeholders This qualitative study involved 26 interviews with informants and review of policy documents that underscores what why and how the Yobe state developed its RIDA The finding showcases the government s mandates objectives and priority agenda setting towards achieving road infrastructure development under the regime Overall the emp has is was primarily placed on both content and context of the regime s RIDA which may positively or negatively affect the state s current and future road infrastructure development
Keywords: policy; infrastructure; road development; agenda setting; yobe state; nigeria